Evaluation of Tetradesmus obliquus and Monoraphidium sp. as potential feedstocks for sustainable biodiesel production - Mofeed, Jelan; Mamdouh, Islam; Eltanahy, Eladl; Shehata, Akram Ismael; Elzaawely, Abdelnaser A.; Teiba, Islam I.; El-Bilawy, Emad H. (Frontiers in Marine Science, 2025)
The escalating global demand for sustainable energy has stimulated research into renewable alternatives, with microalgae emerging as a promising feedstock for biodiesel production. This study evaluates the potential of two microalgal species, Tetradesmus obliquus and Monoraphidium sp., for efficient and sustainable biodiesel synthesis. These species were selected based on their high lipid content, favorable fatty acid profiles, and adaptability to diverse cultivation conditions. Growth optimization experiments under varying nitrogen-to-phosphorus (N:P) ratios and light intensities revealed that balanced N:P ratios (1:1) and moderate light intensity (2.6 klux) significantly enhanced biomass and lipid yields in both species. Monoraphidium sp. achieved higher dry biomass productivity (0.43 g L−¹) and lipid accumulation (50.6%) than T. obliquus (0.105 g L−¹ and 41.8%, respectively). Gas chromatography–mass spectrometry (GC–MS) analysis of fatty acid methyl esters (FAMEs) confirmed the presence of key biodiesel components, including methyl palmitate and methyl oleate, in both species. Biodiesel quality predictions using specialized software indicated that T. obliquus exhibited better oxidative stability and cold flow properties, making it more versatile for varying climates. Monoraphidium sp., however, had higher cetane numbers but poorer cold flow performance. Collectively, these findings highlight the potential of T. obliquus and Monoraphidium sp. as viable candidates for biodiesel production, emphasizing their distinct advantages depending on application requirements. Further research into scalable cultivation and cost-effective extraction methods is essential for industrial implementation.